\[\boxed{\text{504\ (504).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ (2a - b)(2a + b) + b^{2} =\]
\[= 4a^{2} - b^{2} + b^{2} = 4a^{2}\]
\[2)\ 10x^{2} + (y - 5x)(y + 5x) =\]
\[= 10x^{2} + y^{2} - 25x^{2} =\]
\[= y^{2} - 15x^{2}\]
\[3)\ 64m^{2} - (8m + 9)(8m - 9) =\]
\[= 64m^{2} - 64m^{2} + 81 = 81\]
\[= 16x^{2} - 49y^{2} + 49x^{2} - 16y^{2} =\]
\[= 65x^{2} - 65y^{2} = 65 \cdot \left( x^{2} - y^{2} \right)\]
\[= a^{2} + 3a - 2a - 6 + 36 - a^{2} =\]
\[= a + 30\]
\[= 3a^{2} - 3ab - 9a^{2} + 4b^{2} =\]
\[= - 6a^{2} - 3ab + 4b^{2}\]
\[\boxed{\text{504.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ (2x - 3) \cdot (4x + 3) - 8x^{2} =\]
\[= 33\]
\[- 6x = 33 + 9\]
\[- 6x = 42\]
\[x = - 7.\]
\[Ответ:\ x = - 7.\]
\[- 38x = 55 + 30 - 9\]
\[- 38x = 76\]
\[x = - 2.\]
\[Ответ:\ x = - 2.\]
\[3)\ 21x^{2} - (3x - 7) \cdot (7x - 3) =\]
\[= 37\]
\[58x = 37 + 21\]
\[58x = 58\]
\[x = 1.\]
\[Ответ:x = 1.\]
\[2x = 12 - 12 - 2\]
\[2x = - 2\]
\[x = - 1.\]
\[Ответ:x = - 1.\]
\[4x - 10x + 6x = - 2 + 1\]
\[0x = - 1\]
\[Ответ:корней\ нет.\ \]